Quranic Values In Responding To Israeli Aggression In Palestine: A Study Of The Views Of The Indonesian Ulema Council (Mui) Of Medan City - Nasution, Jihan Tuffahati; Amir , Sulaiman Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Israeli-Palestinian conflict is an ongoing global humanitarian crisis that demands a moral response from the Muslim community, including from local religious institutions. This article examines the implementation of Qur'anic values in responding to Israeli aggression against Palestine, focusing on the interpretation and actions of the Indonesian Ulema Council (MUI) of Medan City. This research uses a descriptive qualitative approach with a case study method. Data were collected through semi-structured interviews with MUI scholars of Medan City and document analysis of tafsir and MUI Fatwa No. 83 of 2023. The findings show that the values of war ethics, universal justice, and ukhuwah Islamiyah-contained in QS Al-Baqarah [2]: 190, QS Al-Mumtahanah [60]: 8, and QS Al-Hujurat [49]: 10-is made the normative basis by MUI in formulating attitudes and concrete actions. The implementation of the fatwa in the form of public education, boycott campaigns, moral diplomacy, and donation raising confirms that local Islamic interpretations have a concrete driving force in shaping the solidarity of the ummah. This study emphasizes the importance of the role of regional ulemas in translating the teachings of the Qur'an into contextual and transformative social responses